Glacial heterogeneity in Southern Ocean carbon storage abated by fast South Indian deglacial carbon release - Gottschalk, Julia; Michel, Elisabeth; Thöle, Lena M.; Studer, Anja S.; Hasenfratz, Adam P.; Schmid, Nicole; Butzin, Martin; Mazaud, Alain; Martínez-García, Alfredo; Szidat, Sönke; Jaccard, Samuel L. (Nature Communications, 2020)
Past changes in ocean 14C disequilibria have been suggested to reflect the Southern Ocean control on global exogenic carbon cycling. Yet, the volumetric extent of the glacial carbon pool and the deglacial mechanisms contributing to release remineralized carbon, particularly from regions with enhanced mixing today, remain insufficiently constrained. Here, we reconstruct the deglacial ventilation history of the South Indian upwelling hotspot near Kerguelen Island, using high-resolution 14C-dating of smaller-than-conventional foraminiferal samples and multi-proxy deep-ocean oxygen estimates. We find marked regional differences in Southern Ocean overturning with distinct South Indian fingerprints on (early de-)glacial atmospheric CO2 change. The dissipation of this heterogeneity commenced 14.6 kyr ago, signaling the onset of modern-like, strong South Indian Ocean upwelling, likely promoted by rejuvenated Atlantic overturning. Our findings highlight the South Indian Ocean’s capacity to influence atmospheric CO2 levels and amplify the impacts of inter-hemispheric climate variability on global carbon cycling within centuries and millennia.